TEACHING READING COMPREHENSION USING “SAVE THE LAST WORD FOR ME” STRATEGY TO THE EIGHTH GRADE STUDENTS OF SMP N 7 PALEMBANG - Muhammad Holandiyah; Putri Okva Utami (Edukasi, 2015)
The objective of this study were to find out whether or not there is any significant difference on students’ reading comprehension achievement taught using Save the Last Word for Me strategy and teacher’s method that usually used by the teacher to the eighth grade students of SMP N 7 Palembang. This study used quasi-experimental design using nonequivalent pretest-posttest design. The population of the study was all the eighth grade students of SMP Negeri 7 Palembang. The sample of the study was taken by using convenience sampling method. The total number of the sample was 79 students, 40 students belonged to experimental group and 39 students belonged to control group. In collecting data, the writer used test. The test was given twice to experimental and control groups, as a pretest and posttest. To verify the hypotheses, the data pretest and posttest of the experimental and control groups were analyzed by using independent sample t-test in SPSS program. The finding showed that the p-output (sig.(2-tailed)) was 0.000 lower than 0.05 and the t-value 13.956 was higher than t-table 1.9908. So, it could be stated that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The analysis could infer that there was any significant difference between the students who were taught by using Save the Last Word fo